A Model of Information and Communication Technology Adoption Affecting the Competitive Advantage of Small Enterprises in Thailand - Thongbunyung, Paweena; Jarenvanit , Pensri (KKBS Journal of Business Administration and Accountancy, 2020)
This article aimed to studies: first, the relationship of factors that affect to the adoption of information and communication technology of small enterprises in Thailand; second, creation a model of the Adoption of Information and Communication Technology on the Competitive Advantage of Small Enterprises in Thailand; third, examine the consistency of the model of the Adoption of Information and Communication Technology on the Competitive Advantage of Small Enterprises in Thailand. This research had developed empirical data and used quantitative research by collecting with survey questionnaires 400 samples. The random samples were small enterprises in six provinces in Thailand; Bangkok, Samut Prakan, Chon Buri, Khon Kaen, Surat Thani, and Chiang Mai. Then, the researcher used the structural equation model technique to analyze the assumption and relationship of variables in the conceptual model. The results found that all of the factors; the entrepreneurial passion (EP), Financial costs of using ICT (FIU), competitive pressure of business (CPB), and compatibility of ICT with the organization (CIO) had a positively influenced and significant to the adoption of information and communication technology (AICT). In summary, research shows that AICT has an impact on the Competitive Advantage of small enterprise, including; Low cost, Differentiation of products and services and Quick response to customers. Regarding the benefits of research, the government uses policies that are used to promote and implement ICT in the context of small enterprise to create a competitive advantage. Lastly, entrepreneurs in the private sector can use this research to create a strategic plan for the management of ICT to increase organization performance that allowing small enterprises to operate intense competition in business.